Unveiling Gender Dynamics in Strategic Risk-Taking and Risk-Aversion Among Indonesian Executives - Steven Steven; Dewi Hanggraeni (Green Publisher Indonesia, 2024)
In this research, we aims to examine how gender disparities among corporate leaders (executives) and their level of risk aversion can impact the organization's strategic risk-taking. A questionnaire survey method was employed to collect data from executives in Indonesia holding minimum positions of senior manager (BOD-1), director or commissioner (C-Level). Standard behavioral economics expected utility approach is employed to quantify the degree of risk aversion, while respondents will also make investment choices to assess their inclination towards strategic risk-taking. The research employed the t-test and linear logistic regression analysis to examine the hypothesis. The research findings indicate that female executives exhibit a higher degree of risk aversion compared to their male counterparts. In line with most st udies, risk averse executives prefer to engage in more cautious strategic risk-taking. Nevertheless, there are no discernible disparities between female executives and male execautives when it comes to engaging in strategic risk-taking.